KEDUDUKAN HAKIM WANITA DALAM PERSPEKTIF FUQAHĂ’ (Studi Komparatif Imām Abū Hanīfah dan Ibn Jarīr At-Thabarī) - Siti Mualifah; Adang Djumhur Salikin; Ubaidillah Ubaidillah (Mahkamah : Jurnal Kajian Hukum Islam, 2020)
Judges are a very urgent profession, because judges are one of the highest positions in Islam. This position is higher when compared to the mufti, because the task of the judge is not just to declare the law, but also to impose a sentence in which the results of the decision must be implemented and obeyed. So that the requirements and due diligence must be upheld in a democratic, fair and honest manner. In the discourse on the terms and legal status of women serving as judges, there was a difference of opinion among the jurists and caused controversy among the Imams of the schools. This study aims to answer the questions that formulate the problem: "What is the opinion of Abū Hanīfah and Ibn Jarīr At-Thabarī regarding the position of female judges, how the similarities and differences in opinion of Abū Hanīfah and Ibn Jarīr at-Thabarī regarding the position of female judges and how relevant opinion of the position of female judges in the Indonesian context between Abū Hanīfah and Ibn Jarīr at-Thabarī ”. This study uses qualitative research (literature), the nature of the study used is comparative descriptive analysis, that is by describing the problems associated with and comparing the opinions of two school leaders.The conclusion of this research is that according to Abū Hanīfah, women can be judges only in civil matters (mu’amalah) not in criminal matters (qishās and hudūd), as is the assertion of the ability of a woman to be a witness and the ability of a woman to be a judge. whereas according to Ibn Jarīr at-Thabarī women may be absolute judges for all cases, as Ibn Jarīr at-Thabarī analogizes that women may issue fatwas that are considered valid so that in this case women may be judges and their decisions are considered valid. As for the location of the similarity of the views of Abū Hanīfah and Ibn Jarīr at-Thabarī in terms of the status of women serving as judges that both do not make men the legal requirement for the appointment of a judge. Whereas the difference of opinion between the two is the authority of women judges in deciding cases in the jurisdiction, Abū Hanīfah limits the authority of women in deciding cases only in the civil domain not in hudūd and qishās. In addition, Abū Hanīfah also believes that whoever appoints a woman to be a judge is a sinner. Whereas Ibn Jarīr at-Thabarī allowed women to serve as judges absolutely and related to his appointment he absolutely allowed. Among the opinions of the two imams which is most relevant in Indonesia is the opinion of Ibn Jarīr At-Thabarī which is in accordance with the spirit of the Indonesian people today.